Long‐term successive biochar application increases plant lignin and microbial necromass accumulation but decreases their contributions to soil organic carbon in rice–wheat cropping system - Chen, Zhaoming; He, Lili; Ma, Jinchuan; Ma, Junwei; Ye, Jing; Yu, Qiaogang; Zou, Ping; Sun, Wanchun; Lin, Hui; Wang, Feng; Zhao, Xu; Wang, Qiang (Global change biology. Bioenergy, 2024)
Biochar application is widely recognized as an effective approach for increasing soil organic carbon (SOC) and mitigating climate change in agroecosystems. However, the effects of biochar application on net accumulations and relative contributions of different SOC sources remain unclear. Here, we explored the effects of biochar application on plant‐derived (PDC) and microbial necromass C (MNC) in a 10‐year experimental rice–wheat rotation field receiving four different intensities of biochar application (0, 2.25, 11.5, and 22.5 t ha−1 for each crop season), using phospholipid fatty acids (PLFAs), lignin phenols and amino sugars as biomarkers of microbial biomass, PDC and MNC, respectively. Our results showed that biochar application increased SOC content and stock by 32.6%–203% and 26.4%–145%, respectively. Higher biochar application (11.5 and 22.5 t ha−1) increased soil pH, total nitrogen (TN), total phosphorus (TP), SOC/TN, and root biomass. In addition, higher biochar application enhanced bacterial, fungal, and total microbial biomass. Plant lignin phenols and MNC contents significantly increased, whereas their contributions to SOC significantly decreased with the increase in biochar application rates due to the disproportionate increase in PDC and MNC, and SOC. Fungal necromass had a greater contribution to SOC than bacterial necromass. The fungal/bacterial necromass decreased from 2.56 to 2.26 with increasing biochar application rates, because of the higher abundances of bacteria than that of fungi as indicated by PLFAs under higher biochar application rates. Random forest analyses revealed that pH, TP, and SOC/TN were the main factors controlling plant lignin and MNC accumulation. Structural equation modeling revealed that biochar application increased lignin phenols by stimulating root biomass, whereas enhanced MNC accumulation was primarily from increased microbial biomass and lignin phenols. Overall, our findings suggest that biochar application increases the accumulation of the two SOC sources but decreases their contributions to SOC in paddy soils. Long‐term successive biochar application increases lignin phenols accumulation by stimulating root biomass, whereas biochar application enhanced microbial necromass by increasing microbial biomass and plant lignin. Long‐term biochar application decreases the contributions of plant lignin and microbial necromass to soil organic carbon in paddy soils.